2014
DOI: 10.1539/joh.13-0139-fs
|View full text |Cite
|
Sign up to set email alerts
|

Health Assessment of Self‐employed Hairdressers in France

Abstract: Health Assessment of Self-employed Hairdressers in France: Frederic DESCHAMPS, et al. Occupational Disease Department University Hospital of Reims, France-Objective: Hairdressers have a high incidence of occupational diseases, owing to excessive wet work and exposure to chemical substances. The objective of this study was to assess the prevalence of occupational diseases in a population of self-employed hairdressers, matched for age and sex with a control group of wage-earning hairdressers. Method: A health qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
4
14
6
1
Order By: Relevance
“…About 24 % of the studied hairdressers in the current study reported wheezes. This was lower than previous studies in Norway (37 %) [17] and New Zealand (40 %) [36] while higher than previous prevalence in Turkey (15 %) [34], France (8 and 10 %) [7,19] and Finland (4.8 %) [23].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…About 24 % of the studied hairdressers in the current study reported wheezes. This was lower than previous studies in Norway (37 %) [17] and New Zealand (40 %) [36] while higher than previous prevalence in Turkey (15 %) [34], France (8 and 10 %) [7,19] and Finland (4.8 %) [23].…”
Section: Discussioncontrasting
confidence: 78%
“…This was lower than that was found in New Zealand (29 % for chest tightness) [36], Norway (41 % for breathlessness) [17] and France (29 % for breathlessness) [7].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This could be attributed to some factors such as working environment and organization, long working hours, fewer security measures, and lack of preventive medical measures in work place due to poor training [14]. According to the results, a significant relationship exist between feet structural deformity and BMI so that higher BMI was associated with more structural problems in the feet such as metatarsalgia, hallux rigidus, and flat foot.…”
Section: Discussionmentioning
confidence: 95%
“…Another study showed that the overall health of self-employed hairdressers is lower than that of their wage-earning counterparts. The authors concluded that this can be attributed to several aspects of the workplace and organization, including longer work hours, fewer protective measures and the absence of preventive medicine in the workplace due to lower education (29).…”
Section: Discussionmentioning
confidence: 99%